Shall We Play the Festschrift Game? Essays on the Occasion of Lauri Carlson's 60th Birthday - Santos, Diana; Lindén, Krister; Ng'ang'a, Wanjiku (Springer Berlin Heidelberg : Imprint: Springer, 2012)
There are not many people who can be said to have influenced and impressed researchers in so many disparate areas and language-geographic fields as Lauri Carlson, as is evidenced in the present Festschrift. His insight and acute linguistic sensitivity and linguistic rationality have spawned findings and research work in many areas, from non-standard etymology to hardcore formal linguistics, not forgetting computational areas such as parsing, terminological databases, and, last but not least, machine translation. In addition to his renowned and widely acknowledged insights in tense and aspect and its relationship with nominal quantification, and his ground-breaking work in dialog using game-theoretic machinery, Lauri has in the last fifteen years as Professor of Language Theory and Translation Technology contributed immensely to areas such as translation, terminology and general applications of computational linguistics. The three editors of the present volume have successfully performed doctoral studies under Lauri's supervision, and wish with this volume to pay tribute to his supervision and to his influence in matters associated with research and scientific, linguistic and philosophical inquiry, as well as to his humanity and friendship.